Remission outcomes in severe eosinophilic asthma with mepolizumab therapy: Analysis of the REDES study - Pavord, Ian; Gardiner, Frances; Heaney, Liam G.; Domingo, Christian; Price, Robert G.; Pullan, Alison; Oppenheimer, John; Brusselle, Guy; Nagase, Hiroyuki; Chupp, Geoffrey; Pizzichini, Emilio; Bañas-Conejero, David; et al. (Frontiers in Immunology, 2023)
Clinical remission as a multicomponent treatment goal in severe asthma is being explored in clinical practice. This post hoc analysis used data from the REDES study to assess the proportion of patients with severe eosinophilic asthma achieving our multicomponent definitions of clinical remission after 1 year of mepolizumab treatment. The real-world, retrospective observational REDES study enrolled patients with severe eosinophilic asthma who were newly prescribed mepolizumab and with ≥12 months of medical records pre-enrolment. Multicomponent clinical remission was defined as: oral corticosteroid (OCS)-free; exacerbation-free; asthma control test (ACT) score ≥20; and with or without post-bronchodilator forced expiratory volume in 1 second ≥80%. Baseline characteristics were also assessed in those who did/did not achieve clinical remission. 37% and 30% of patients with severe eosinophilic asthma met our proposed three- and four-component on-treatment clinical remission definitions; an increase from 2% and 3% at baseline. Most frequently achieved individual components of clinical remission were: OCS-free; ACT score ≥20. For patients fulfilling the multicomponent clinical remission definitions, at baseline we observed higher blood eosinophil counts, better ACT scores and lung function, lower maintenance OCS use, and a slightly lower rate of prior exacerbations versus those who did not. Clinical remission is a realistic target in clinical practice for a subset of patients with severe eosinophilic asthma receiving mepolizumab. Further studies are required to elucidate whether features linked to the underlying endotype can help predict treatment outcomes, increase rates of clinical remission, and potentially modify disease progression. Funding: GSK (213172)